Embryonic Chicken Transplantation is a Promising Model for Studying the Invasive Behavior of Melanoma Cells - Jayachandran, Aparna; McKeown, Sonja J.; Woods, Briannyn L.; Prithviraj, Prashanth; Cebon, Jonathan (Frontiers in Oncology, 2015)
Epithelial-to-mesenchymal transition is a hallmark event in the metastatic cascade conferring invasive ability to tumor cells. There are ongoing efforts to replicate the physiological events occurring during mobilization of tumor cells in model systems. However, few systems are able to capture these complex in vivo events. The embryonic chicken transplantation model has emerged as a useful system to assess melanoma cells including functions that are relevant to the metastatic process, namely invasion and plasticity. The chicken embryo represents an accessible and economical 3-dimensional in vivo model for investigating melanoma cell invasion as it exploits the ancestral relationship between melanoma and its precursor neural crest cells. We describe a methodology which enables the interrogation of melanoma cell motility within the developing avian embryo. This model involves the injection of melanoma cells into the neural tube of chicken embryos. Melanoma cells are labelled using fluorescent tracker dye, Vybrant DiO, then cultured as hanging drops for 24 hours to aggregate the cells. Groups of approximately 700 cells are placed into the neural tube of chicken embryos prior to the onset of neural crest migration at the hindbrain level (embryonic day 1.5) or trunk level (embryonic day 2.5). Chick embryos are reincubated and analysed after 48 hours for the location of melanoma cells using fluorescent microscopy on whole mounts and cross-sections of the embryos. Using this system, we compared the in vivo invasive behavior of epithelial-like and mesenchymal-like melanoma cells. We report that the developing embryonic microenvironment confers motile abilities to both types of melanoma cells. Hence the embryonic chicken transplantation model has potential to become a valuable tool for in vivo melanoma invasion studies. Importantly, it may provide novel insights into and reveal previously unknown mediators of the metastatic steps of invasion and dissemination in melanoma.